Banking theory and practice : (law and foreign exchange) - Shekhar, K.C. (New Delhi: Vikas Publishing House PVT Ltd, 2000)
The book is divided into three major parts. Part I provides the study of commercial banking theory; part II provides the institutional background for the study of Central Banking; part III deals with practical banking with reference to the Indian Negotiable Instrument Act.
Four new chapters and two appendices have been added to this edition.
osc 11/04/2017; nmn 30/05/2019
Loans
Keywords: Banks and banking; Central Banking; Banking Law